Theodor Mommsen and the collegia funeraticia - Przemysław Wojciechowski (Klio)
In 1843, Theodor Mommsen completed his legal studies at the University of Kiel; in the same year, his dissertation De collegiis et sodaliciis Romanorum appeared in print. This publication, which was small in terms of volume, not only opened the door to an illustrious academic career for its author, but also had an enormous impact on the course of scholarly discussion on Roman colleges. One of the basic concepts used in this discussion is the 'funeral colleges' created by Mommsen. The main purpose of this article is to show that we are dealing with an anachronism in this case. Mommsen's proposed concept of 'funeral colleges' found very fertile ground in Germany at the time ('bürgerliche Vereinsbewegung' and Bismarck's social reforms), but it is not substantiated by the source material. None of the known Roman colleges was a 'funeral college' in the sense in which the term was used by Mommsen and his scholarly heirs. The fact that, for many colleges, helping to organise the burial of a deceased member was an important sphere of their activity does not make them 'funeral colleges'.